Rancang Bangun Sistem Pemberi Pakan Ikan di Kolong Bekas Tambang Timah Secara Otomatis Berbasis IoT - Ocsirendi, Ocsirendi; Sulistyo, Eko; Dwisaputra, Indra; Ainin, Dewi Tumatul; Susanto, Dedi; Ramli, Ramli (Manutech : Jurnal Teknologi Manufaktur, 2025)
This study aims to design and develop an automatic fish feeding system based on the Internet of Things (IoT) that can be applied in former tin mining pits in Bangka Belitung. The system is expected to improve feeding efficiency and reduce dependence on manual labor. The research method includes hardware design using a NodeMCU ESP32 microcontroller, a servo motor as the feed dispensing actuator, and an RTC module as the time controller. The system is equipped with a web-based IoT application for remote control and monitoring. Testing was carried out at a fish farming site located in a former mining pond, with observations on feeding schedule accuracy, feed throwing distance, and feed usage efficiency. The results showed that the system achieved 100% accuracy in feed timing based on RTC sensor readings. Feed output during multiple feeder motor rotations was stable, with an error rate of less than 1%. The pellet throwing distance at 90% motor speed reached a maximum of 6.6 meters and a minimum of 2.4 meters.The system can also be controlled remotely via the web, allowing users to schedule feeding times and monitor device status in real time from a smartphone or computer. This system has proven to be effective and feasible for freshwater fish farming in post-mining areas, supporting sustainable aquaculture development.